Analysis of Coffee Agroindustry in Lampung: Literature Review of Potential and Production Challenges - Fitiryanti, Jeni; Agustina Hasibuan, Adelia; Putri Rahayu, Intan; Sanjaya, Vicky F (Dinamis : Journal of Islamic Management and Bussiness, 2025)
This study examines the potential and challenges of the coffee agroindustry in Lampung Province through a literature review. As one of the largest coffee producers in Indonesia, Lampung excels in robusta coffee production, with major hubs such as West Lampung and Tanggamus. Despite its significant potential, Lampung's coffee agroindustry faces constraints, including low coffee bean quality, supply chain inefficiencies, limited market access, and suboptimal promotion. Strategic approaches, such as cultivation innovation, post-harvest quality improvement, supply chain coordination, and diversified marketing strategies, are essential to ensure the sustainability and competitiveness of this industry. These findings provide valuable insights for the sustainable development of Lampung's coffee agroindustry